Statin Therapy Is Associated with Reduced Risk of Peptic Ulcer Disease in the Taiwanese Population - Chih-Ho Lai; Chih-Ho Lai; Chih-Ho Lai; Chih-Ho Lai; Chia-Hung Kao; Chia-Hung Kao; Chia-Hung Kao; Chun-Jung Lin; Chun-Jung Lin; Wei-Chih Liao; Wei-Chih Liao; Yu-An Chen; et al. (Frontiers Media S.A., 2017)
Although statin use may affect the severity of chronic gastritis and gastric cancer, no data exists about the relationship between statin therapy and risk of peptic ulcer disease (PUD) in patients. We investigated the effect of statin use and the incidence of PUD from the Taiwan National Health Insurance Research Database (NHIRD). A total of 35,194 patients records for medical claims were enrolled. We performed a population-based case-control analysis to compare the incidence of PUD in patients who were prescribed statins and that in patients who were not. In the univariate logistic analysis, we found that statin was not significant risk of PUD. However, a multivariate model indicates that satin use was significantly associated with a reduced risk of PUD (adjusted odds ratio [aOR] = 0.87, 95% CI = 0.82-0.93, P < 0.001). The cumulative defined daily dose (DDD) was analyzed. Patients who prescribed fluvastatin ≥280 DDD, atorvastatin ≥200 DDD, and pravastatin ≥130 DDD dramatically decreased risk for PUD (aOR = 0.58, 0.67, and 0.71; 95% CI = 0.46-0.74, 0.57-0.78, and 0.56-0.91, respectively). Our results showed that statin therapy reduced the risk of PUD and this was associated with the high cumulative DDD of prescribed statins. This study reveals that active use of statins to be associated with decreased risk for PUD.